Bonita delgada, más delgada...más bonita - Alzate, Gabriel Jaime (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2012)
Of the four months he spent at that base, he remembers the first weapon he got his hands on, a 1936 rifle used during the civil war. It was one of the most exciting things he experienced, so at first he decided to become a gunner. Then he was transferred to Astorga where, already as a professional soldier, he began to be assigned missions. He didn't like the place very much, but it was there that he started his first combat without direct fire. He was in several bases during the next three years, and was sent to secret missions in Kosovo and Lebanon, where he came to know what it was like to cross fires and risk his life for the conviction of defending a country he already felt as his own.